Konflik Penolakan Pembangunan Gereja Methodist dalam Perspektif Sosiologis di Desa Pematang Seleng, Kabupaten Labuhanbatu - Putri, Widya; Irwansyah, Irwansyah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
\This study aims to analyze the conflict surrounding the rejection of the Methodist Church construction in Pematang Seleng Village, Labuhanbatu Regency, from a sociological perspective. Using a qualitative approach with a case study method, data were gathered through observations, interviews, and literature reviews. The findings reveal that the conflict is driven by socio-cultural, political, economic, and religious factors. Socio-cultural factors are related to the norms and values of the predominantly Muslim local community, while political factors encompass both local and national interests. Economic factors include concerns over the potential depletion of local economic resources, and religious factors involve fears of Christianization and religious disparities. The conflict exemplifies the complexity of inter-religious relations in Indonesia, underscoring that tolerance and pluralism remain significant challenges. The study recommends resolving the conflict through inter-religious dialogue, education on tolerance and pluralism, law enforcement, and governmental efforts to promote harmonious inter-religious relations.